2015
DOI: 10.1097/ico.0000000000000354
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Prospective, Single-Masked Clinical Trial of Endothelial Keratoplasty Performance With 2 Donor Cornea 4°C Storage Solutions and Associated Chambers

Abstract: Endothelial cell loss and graft success were comparable at 6 months for paired donor corneas stored in Optisol GS and Life4°C.Clinical Trial Registration-URL: http://www.clinicaltrials.gov. Unique identifier: NCT01657500.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In 2013, of the 62,274 USA-generated donor tissues for either PKP or EK, 18,355 (29%) were exported. 5 The introduction of Life 4°C (Numedis, Isanti, MN) in the United States in 2010, another chondroitin-based intermediate storage medium approved by the FDA for 14-day PT with reportedly improved endothelial viability, 29 has also not had an impact on this domestic practice pattern, because it represents only a small percentage of the 4°C storage solutions used by eye banks.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, of the 62,274 USA-generated donor tissues for either PKP or EK, 18,355 (29%) were exported. 5 The introduction of Life 4°C (Numedis, Isanti, MN) in the United States in 2010, another chondroitin-based intermediate storage medium approved by the FDA for 14-day PT with reportedly improved endothelial viability, 29 has also not had an impact on this domestic practice pattern, because it represents only a small percentage of the 4°C storage solutions used by eye banks.…”
Section: Discussionmentioning
confidence: 99%
“…Price et al stored the tissues randomly in Life4°C or Optisol-GS for a maximum period of 7 days to be used for EK. 37 There was no difference between Life4°C and Optisol-GS groups in terms of endothelial cell loss (ECL) at 6 months after the surgery (18% and 20% ECL from Life 4°C and Optisol-GS group respectively). Recipients' stroma and grafts remained clear during the 6-month follow-up.…”
Section: Hs For Ekmentioning
confidence: 89%
“…Although it was suggested that Life4°C behaves similar to Optisol-GS, it has been shown that the addition of glutathione in Optisol-GS facilitates the performance and prolongs the quality of the graft. 37 Lass et al 39 showed that after 3 years of follow-up, the ECL was 37.3% and 39.7% when the tissues were stored for 0-7 days and 8-14 days respectively, which was found to be statistically different.…”
Section: Hs For Ekmentioning
confidence: 98%
See 1 more Smart Citation
“…Resource centers with similar roles for other types of images have become common as new imaging methods have been developed and implemented clinically to monitor the effects of treatment. They have been widely used in oncology (Chauvie et al 2014;Gopal et al 2016) and ophthalmology trials (Siegel and Milton 1989;Danis 2009;Price et al 2015;Toth et al 2015;Domalpally et al 2016;Rosenfeld et al 2018) but also in trials in other medical settings (Desiderio et al 2006;Ahmad et al 2016).…”
Section: Other Resource Centersmentioning
confidence: 99%